Frequency of Ventilator Associated Pneumonia in Patients Admitted at a Tertiary Care Hospital of Pakistan - Javed, Hamna; Baqai, Haider Zaigham; Hassan, Fahad; Afzal, Ayesha (Infectious Diseases Journal of Pakistan, 2022)
Objective: To determine the frequency and outcome of Ventilator Associated Pneumonia (VAP) in patients requiring mechanical ventilation (MV) admitted at the Intensive Care Unit (ICU) of a tertiary care hospital in Pakistan. Methods: This descriptive cross-sectional study was done at Benazir Bhutto Hospital Rawalpindi within a duration of 8 months from April-2019 to Dec-2019. We included 150 adult patients of age >20 years from ICU of hospital who were on MV for > 2 days. The diagnosis of VAP was made according to the criteria given by IDSA/ATS guidelines. The frequency, microbial spectrum and outcomes of VAP patients were noted for each patient. Results: Mean age of patients was 51.4±11.7 years. There were 107 (71.3%) male patients. VAP was diagnosed in 23 (15.3%) patients, of which 09 (6.0%) patients developed early VAP while 14 (9.3%) developed late VAP. Sepsis occurred in 08 (34.7%) VAP patients versus 22 (17.3%) in non-VAP patients (p-value 0.05), tracheostomy was done in 4 (17.3%) VAP patients versus 1 (0.78%) non-VAP patients (p-value <0.0001), re-intubation done in 8 (34.7%) VAP patients versus 10 (7.8%) non-VAP patients (p-value <0.0001). There was no significant difference in mortality in VAP and non-VAP patients. Common microbes causing VAP were P. aeruginosa isolated in 08 (34.7%) patients, A. baumannii in 05 (21.7%), MRSA in 04 (17.3%) patients. Conclusion:Ventilator associated pneumonia is a serious and common complication in patients who require prolonged ventilation. VAP considerably increase the morbidity and mortality in ventilated patients. In present study, P. aeruginosa, A. baumannii and MRSA were microbes causing VAP in ventilated patients. Keywords: Ventilator a pneumonia, Microbial spectrum.